ILLOCUTIONARY ACT FOUND IN A BOX OF HOPE MOVIE - Duha, Herlian (Research on English Language Education, 2023)
Language is the most important tool for human to share knowledge and idea. The way people used language to covey messages and idea in certain society is studied in pragmatics. sometimes, people do not only convey messages by using utterance, instead they use utterances to make someone perform action which is called illocutionary act. The aims of this research were to find out the classification of illocutionary act in A Box of Hope Movie and the meaning of each sentence that has been classified in illocutionary act. The researcher focused on analyzing illocutionary act based in Searle’s five category of illocutionary act; representatives, directives, commissives, expressives, and declarations. This research was designed in descriptive qualitative research which focused on the analysis of Illocutionary act. The result showed that there are five types of illocutionary act found in A Box of Hope Movie. The total of illocutionary found in the movie is 233 utterances, 57 representatives, 74 directives, 52 commissives, and only 2 declarations. The meaning of illocutionary act found in the movie often leads to perform an action and sometimes does not always correspond to the literal meaning. It can be concluded that all the types of Searle’s five category of illocutionary act were found in A Box of Hope Movie and the meaning of each illocutionary act can be interpreted based on the listener interpretation toward the utterance.